2022
DOI: 10.3390/antiox11050829
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Lipid Metabolism Dysregulation by Selenium and Folic Acid Co-Supplementation to Mitigate Pathology in Alzheimer’s Disease

Abstract: Aberrant lipid metabolism is reported to be closely related to the pathogenesis of neurodegenerative diseases, such as Alzheimer’s disease (AD). Selenium (Se) and folate are two ideal and safe nutritional supplements, whose biological effects include regulating redox and homocysteine (Hcy) homeostasis in vivo. Here, to achieve effective multitarget therapy for AD, we combined Se and folic acid in a co-supplementation regimen (Se-FA) to study the therapeutic potential and exact mechanism in two transgenic mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Secondly, the anti-inflammatory effect of folate [ 47 ] may also be a mechanism for decreasing the risk of functional disability [ 48 , 49 ]. In addition, folate as a coenzyme of one-carbon metabolism involved homocysteine methylation and promotes homocysteine to methionine conversion [ 50 , 51 , 52 ]. Several studies have suggested that elevated homocysteine levels may be a risk factor for functional disability [ 17 ] or physical function decline [ 18 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the anti-inflammatory effect of folate [ 47 ] may also be a mechanism for decreasing the risk of functional disability [ 48 , 49 ]. In addition, folate as a coenzyme of one-carbon metabolism involved homocysteine methylation and promotes homocysteine to methionine conversion [ 50 , 51 , 52 ]. Several studies have suggested that elevated homocysteine levels may be a risk factor for functional disability [ 17 ] or physical function decline [ 18 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 3× Tg-AD mice (B6; 129-Psen1tm1MpmTg (APPSwe, tauP301L) 1 Lfa/J), as described previously [ 19 ], were purchased from The Jackson Laboratory (Bar Harbor, ME). They were housed in cages with free access to food and water at 22 ± 2 °C under a 12 h alternating light/dark cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Untargeted metabolomic analysis after Se supplementation have been performed using mice models [47,73,[85][86][87][88][89][90][91][92][93][94][95][96][97][98], pigs [99][100][101][102], broilers [103], cells [104], rats [105][106][107], gazelle [108], zebra fish [109], humans [110], donkeys [111], salmon [112], and catfish [113]. These studies reported a wide range of altered metabolites after Se supplementation focused on liver [73, 91, 94-96, 100-102, 105, 112] and plasma/serum metabolism [73,92,96,101,105,108,110], but also in muscle [99,103], kidneys [73,93], testes [73], lungs [73,90], spleen [96], blood…”
Section: Metabolomic Studies Related To the Impact Of Dietary Seleniu...mentioning
confidence: 99%
“…A summary of the metabolomics studies reported after Se supplementation using different analytical platforms is shown in Table 2. As can be seen, metabolomics is usually combined with transcriptomics [47,90,94,99,101,103,109,111], histopathology [98,103,106,109], metallomics [73,90,91,98,99,105,107], proteomics [96,101], enzymatic activities [91,97,98], or targeted metabolomics [100,109]. Several studies focused on metataxonomics and gut metabolomics [95,96,101,106,113].…”
Section: Metabolomic Studies Related To the Impact Of Dietary Seleniu...mentioning
confidence: 99%
See 1 more Smart Citation